Glutamate enhances the production of inflammatory cytokines IL-6 and IL-11, as well as chemokines CXCL2, CXCL3, and CXCL8 in keloid fibroblasts - Chen, Yan; Xu, Yaohan; Zhang, Jiahe; Feng, Chenxi; Chen, Jie; Song, Yinjing; Pan, Jing; Zhu, Jiang; Cheng, Hao (Frontiers in Molecular Biosciences, 2026)
IntroductionKeloids are fibroproliferative skin scars characterized by excessive extracellular matrix deposition and a high rate of recurrence. Despite extensive research, their pathogenesis remains incompletely understood and effective curative therapies are lacking.MethodsRNA sequencing (RNA-seq) and metabolomics were performed to compare gene expression and metabolite profiles between human keloid tissues and normal skin. Single-cell RNA sequencing, immunohistochemistry, and immunofluorescence were used to determine the cellular localization of key genes. In vitro, human fibroblasts were stimulated with glutamate, followed by RNA-seq, quantitative RT-PCR, and ELISA to evaluate inflammatory gene expression and cytokine secretion.ResultsTranscriptomic analysis revealed significant enrichment of the neuroactive ligand-receptor interaction pathway in keloid tissue, with marked upregulation of the glutamate receptor subunit GRIN2D. Single-cell and histological analyses demonstrated that GRIN2D is predominantly expressed in fibroblasts. Metabolomic profiling showed significantly increased levels of glutamate and glutamine in keloid tissues. Glutamate stimulation of fibroblasts significantly enhanced the expression and secretion of inflammatory cytokines IL-6 and IL-11, as well as chemokines CXCL2, CXCL3, and CXCL8 (IL-8).DiscussionThese results underscore the crucial role of glutamate metabolism in promoting the infammatory functions of fbroblasts. They suggest that glutamate contributes to keloid progression and provides a theoretical basis for targeting glutamte signaling pathway in keloid treatment.